Computer-aided continuous drug infusion setup and test of a mobile closed-loop system for the continuous automated infusion of insulin. - Dudde, R. (IEEE Transactions on information technology in biomedicine)
For a diabetes mellitus patient, tight control of glucose level is essential. Results are reported of an investigation of the suitability of existing wearable continuous insulin infusors controlled and adjusted by a control algorithm using continuous glucose measurements as input to perform the functionality of an artificial pancreas. Special attention was given to the development of a continuous glucose monitor and to evaluate which quality of input data is necessary for the control algorithm. In clinical trials, it was found that for patients in a controlled environment an autonomously regulating control algorithm leads to an improved adjustment of patient glucose values and less overall insulin infusion as compared with the best fixed preprogrammed insulin infusion profiles of standard pump therapy. For the limited number of cases studied here, functionality of the control algorithm could tolerate some delay between the actual glucose values in the patient interstitial fluid and the algorithm input of up to 30 min. A quasicontinuous glucose measurement delivering actual glucose values every 5-10 min seems to be suited to control an artificial pancreas